STUDI KASUS PENERAPAN KURIKULUM KTSP SENI BUDAYA DI MAN 2 KOTO BARU - Angge Pratiwi Vitri; Zora Iriani; Indrayuda Indrayuda (FBS Universitas Negeri Padang, 2012)
This article aims to describe a case study in the implementation of cultural arts curriculum of KTSP in MAN 2 Koto Baru Solok. This type of research is a qualitative descriptive method. Object of research is the study of dance in MAN 2 Koto Baru, data were collected through interviews, literature study and direct observation. Data analysis was performed with phenomenology analysis and relationship between components. The results showed, the cases that occurred in KTSP curriculum implementation. Which one KTSP curriculum is not implemented fully in MAN 2 Koto Baru, so some elements like dance practice can not function . This is influenced by the school's policy that based on Islam. This means that the KTSP curriculum be implemented incomplete. On the other hand, MAN 2 Koto Baru which is a school of DEPAG supervision, and neither has the cultural arts curriculum. Therefore, the cultural arts curriculum implementation of KTSP into a case in MAN 2 Koto Baru.